Preparing for the European Structural Funds' next funding period - Astrid Ziegler (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2006)
Chapter 1 addresses central challenges (population and employment developments, innovative capacity) and highlights, in the view of the evaluators, the problem areas for the new funding period. This is followed, in Chapter 2, by an overview of the current funding period and an excursive outline of the adjustments still being recommended for the current funding programme. Chapter 3, which forms the core focus of this paper, discusses the recommendations proposed by evaluators on the cross-national direction of European structural funding from 2007 onwards. Chapter 4 provides the Conclusion for this discussion paper.
Keywords: 330